Computation of Green's matrices for boundary value problems associated with a pair of mixed linear regular ordinary differential operators - T. Gnana Bhaskar; M. Venkatesulu (International Journal of Mathematics and Mathematical Sciences)
An algorithm for the computation of Green's matrices for boundary value problems associated with a pair of mixed linear regular ordinary differential operators is presented and two examples from the studies of acoustic waveguides in ocean and transverse vibrations in nonhomogeneous strings are discussed.